Implementasi Pemasaran Digital melalui Media Sosial dan E-Commerce Internasional pada UMKM Lovebysisdaisy - Agustina Agustina; Wisnu Yuwono; Erilia Kesumahati (Jurnal Kemitraan Masyarakat, 2025)
Lovebysisdaisy is a micro, small, and medium enterprise (MSME) producing handmade phone charm accessories and operating as a home-based business with limited digital marketing capabilities. This community service program aimed to strengthen digital marketing through Instagram optimization and the utilization of Shopee as an e-commerce platform. A participatory approach was applied, involving the business owner from problem identification to evaluation. Methods included observation, interviews, and digital documentation, followed by assistance in content development and Shopee store management. The results show that structured Instagram content improved visual consistency and audience engagement, while the establishment of a Shopee store enabled organized product catalogs and initial customer interactions. These outcomes indicate increased digital awareness and readiness of the MSME to implement sustainable online marketing strategies and expand market access.